Cryptosporidium spp. in groundwater supplies intended for human consumption – A descriptive review of global prevalence, risk factors and knowledge gaps. (1st June 2020) - Chique, C.; Hynds, P.D.; Andrade, L.; Burke, L.; Morris, D.; Ryan, M.P.; O'Dwyer, J.
Abstract: Cryptosporidiosis is one of the leading causes of diarrhoeal illness and mortality induced by protozoan pathogens worldwide. As a largely waterborne disease, emphasis has been given to the study of Cryptosporidium spp. in surface waters, readily susceptible to pathogenic contamination. Conversely, the status of Cryptosporidium in potable groundwater sources, generally regarded as a pristine and "safe" drinking-water supply owing to (sub)-soil protection, remains largely unknown. As such, this investigation presents the first literature review aimed to ascertain the global prevalence of Cryptosporidium in groundwater supply sources intended for human consumption. Thirty-seven peer-reviewed studies were identified and included in the review. Groundwater sample and supply detection rates (estimated 10–20%) indicate Cryptosporidium is frequently present in domestic groundwater sources, representing a latent health concern for groundwater consumers. Specifically, sample (10.4%) and source (19.1%) detection rates deriving from comprehensive "temporal" investigations are put forward as representative of a contamination 'baseline' for Cryptosporidium in 'domestic' groundwater supplies. Proposed 'baseline' prevalence figures are largely applicable in preventive risk-based catchment and groundwater quality management including the formulation of Quantitative Microbial Risk Assessment (QMRA). Notwithstanding, a large geographical disparity in available investigations and lack of standardized reporting restrict the transferability of research findings. Overall, the mechanisms responsible for Cryptosporidium transport and ingress into groundwater supplies remain ambiguous, representing a critical knowledge gap, and denoting a distinctive lack of integration between groundwater and public-health sub-disciplines among investigations. Key recommendations and guidelines are provided for prospective studies directed at more integrative and multi-disciplinary research. Graphical abstract: Image 1 Highlights: Global review of Cryptosporidium spp. prevalence in 'domestic' groundwater sources. Cryptosporidium frequently occurs in groundwater sources and is a latent health concern. Critical lack of understanding of Cryptosporidium transport into groundwater sources evident. Highly applicable Cryptosporidium groundwater contamination 'baselines' estimated. Need to integrate groundwater and public-health research for improved prevalence insights.